Evidence for Locus Heterogeneity in Autosomal Dominant Limb-Girdle Muscular Dystrophy - Speer, Marcy C. (1995)
Limb-girdle muscular dystrophy (LGMD) is a diagnostic classification encompassing a broad group of proximal myopathies. A gene for the dominant form of LGMD (LGMD1A) has recently been localized to a 7-cM region of chromosome 5q between D5S178 and IL9. We studied three additional dominant LGMD families for linkage to these two markers and excluded all from localization to this region, providing evidence for locus heterogeneity within the dominant form of LGMD. Although the patterns of muscle weakness were similar in all families studied, the majority of affected family members in the chromosome 5–linked pedigree have a dysarthric speech pattern, which is not present in any of the five unlinked families. The demonstration of heterogeneity within autosomal dominant LGMD is the first step in attempting to subclassify these families with similar clinical phenotypes on a molecular level.